The gluttons of eastern Siberia. Spirits, poachers, and cannibals in Evenki perceptions - Brandišauskas, Donatas (Études mongoles et sibériennes, centrasiatiques et tibétaines, 2018)
In this article, I intend to show how the sociocultural changes that occurred during the Soviet period as well as current challenges are creatively reflected and incorporated into Evenki cosmology. Various malevolent beings to whom gluttony and, in some cases, anthropophagi have existed in Evenki cosmology for centuries. Today, these beings are continuously encountered in daily life and depicted in contemporary Evenki narrations. While references to the cannibalistic features of indigenous peoples were widely employed by colonial powers, today the Evenki link the influence of malevolent beings with past and current state policies, tragic events, ruptures of ethical norms, the exploitation of resources, and personal misbehaviour. These narrations enable the Evenki to promote awareness of potential dangers and teach other people appropriate moral behaviour and judgements. Dans cet article, je tente de montrer comment les changements socioculturels survenus pendant la période soviétique ainsi que les défis actuels sont reflétés avec créativité et incorporés dans la cosmogonie des Évenks. Les nombreux êtres malveillants existant depuis des siècles dans la cosmogonie évenke et ayant pour attributs la gloutonnerie, et dans certains cas l’anthropophagie, sont continuellement rencontrés dans la vie quotidienne et décrits dans les récits contemporains évenks. Alors que les références au cannibalisme des peuples autochtones ont été largement employées par le pouvoir colonial, aujourd’hui, les Évenks lient l’influence des êtres malveillants aux politiques étatiques passées et présentes, aux événements tragiques et aux transgressions individuelles des normes éthiques et des règles de conduite. Raconter ou participer à la narration, permet aux Évenks de promouvoir la conscience des dangers potentiels, tout en enseignant les convenances en termes d’attitudes et de jugements moraux.